## Expanding the Expression (a + 3)(a - 2)

This expression involves multiplying two binomials. We can achieve this by applying the **FOIL method**, which stands for **First, Outer, Inner, Last**.

**Here's how it works:**

**First:**Multiply the first terms of each binomial:*a**a*=*a²***Outer:**Multiply the outer terms of the binomials:*a**-2*=*-2a***Inner:**Multiply the inner terms of the binomials:*3**a*=*3a***Last:**Multiply the last terms of each binomial:*3**-2*=*-6*

**Combining the results:**

(a + 3)(a - 2) = a² - 2a + 3a - 6

**Simplifying:**

(a + 3)(a - 2) = **a² + a - 6**

Therefore, the expanded and simplified form of (a + 3)(a - 2) is **a² + a - 6**.